Interacting constituents in cosmology - Aldrovandi, R. [UNESP]; Cuzinatto, R. R. [UNESP]; Medeiros, L. G. [UNESP] (World Scientific Publishing, 2008)
Universe evolution, as described by Friedmann's equations, is determined by source terms fixed by the choice of pressure × energy density equations of state p(ρ). The usual approach in cosmology considers equations of state accounting only for kinematic terms, ignoring the contribution from the interactions between the particles constituting the source fluid. In this work the importance of these neglected terms is emphasized. A systematic method, based on the statistical mechanics of real fluids, is proposed to include them. A toy model is presented which shows how such interaction terms could be applied to engender significant cosmological effects. © 2008 World Scientific Publishing Company.
Keywords: Cosmology; Equation of state; Statistical mechanics